Perubahan Golongan Darah Berdasarkan Pengaruh Waktu dan Mikroorganisme Yang Berperan - Muhamad Masyrur; I Ketut Junitha; Meitini W. Proborini (Metamorfosa: Journal of Biological Sciences, 2019)
Blood is one of the most important evidence in the forensic analysis. Blood has a special characteristic or identity of the owner. Blood can be analyzed blood type to know the owner of the blood. But in the course of time, the blood will be degraded so it will be change of blood type into blood type O. One of the contributing factors is the presence of microorganisms that it grow in the blood. The material of this research is the human blood of blood type A, B, AB and O from 4 (four) respondents of 3 (three) males and 1 (one) female who are 20 to 40 years old. Each sampel of 150 µL was dropped on sterile gauze size 2 x 6 cm, then it was dried. Sample were stored at room temperature (± 30 oC) for 0, 30, 60, 90 and 120 days. Sampel was tested for blood type using absorption elution method based on the work instructions from The Police Forensic Laboratory of Denpasar Branch in 2016. The results of this research indicate that the human dried blood stored on sterile gauze media for 30 and 60 days has not changed its blood type. Storage of the human dried blood for 90 and 120 days, it have changed blood type with found antigen A or B that was not detected back through absorbtion elution analysis on blood group A, B and AB. This research found 9 species of fungi and 7 species of bacteria that they grow on the blood samples. Species of Fungi and bacteria that have high ability to degrading all blood group (A, B and AB) are Acromonium carticola, Alternaria alternata, Aspergillus flavus, Aspergillus niger, Penicillium sp and Bacillus coagulans. While species of fungi and bacteria that have high ability to degrading blood group B or AB are Fusarium sp, Trichoderma harzianum, Trichoderma viridae, Bacillus sp and Staphylococcus cohnii.